On-farm evaluation of growth and reproductive performance of timorensis deer kept in Taman Pertanian Universiti, Universiti Putra Malaysia, Selangor - Zakaria, Muhamad Alif (2015)
A retrospective study was conducted to evaluate the health and reproductive performances of timorensis deer kept in Field 16, Taman Pertanian Universiti. The farm was built with the aim of being a model farm for teaching, public exhibition, and a model for farmers. This study involved all timorensis deer kept at the farm. Available farm records between 2011 and 2014 were collected and analysed. However, the age at first fawning, mean birth weight (kg), fawning intervals, litter size, age at first parturition and parturition interval (months) could not be analysed since the records were not kept. Most fawning occurred between October and December each year with apparent peak in December. The mean fawning percentage for the past 4 years was 60% while the average rate of mortality was low (<10%). The average daily gain was 0.02±0.02 kg (n=140) and there was no significant (P>0.05) difference between the average monthly ADG every year. The risk factors particularly the monthly rainfall showed significant (p<0.05) negative correlation with the monthly ADG but positive correlated with monthly rate of fawning (p<0.05). Therefore, there might be a breeding season within the mild dry months of February to March that resulted in fawning season in the rainy months of October to December. Thus, the farm should recognize these seasons to take appropriate actions in preparing hinds for breeding and farmhands in handling fawning.